2014
DOI: 10.3329/jbau.v11i2.19941
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and gonado-somatic index of wild freshwater spiny eel Mastacembelus armatus (Lacepede) from Kishoreganj region of Bangladesh

Abstract: Fecundity and gonado-somatic index (GSI) of wild freshwater spiny eel Mastacembelus armatus were estimated from haor region of Kishoreganj district of Bangladesh. Estimated fecundity ranged from 2,235 to 19,493 for the fish measuring from 25 to 54 cm and weighing from 79 to 345 g. The minimum, median and maximum ova diameter was 0.20, 1.90 and 2.20 mm, respectively. The average numbers of ova present per g body weight were 45.41±8.85, 46.93±15.00 and 47.52±8.32 while the average numbers of ova present per g ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Sicyopterus longifilis and B. belobranchus have been identified as the two species constituting Nike fish according to Sahami et al (2019). While A. grammepomus has not been previously reported as part of Nike fish, the assumption is made in this research based on the indication in Ali et al (2015) that A. grammepomus is an amphidromous species. Thus, it is considered that these three species collectively make up Nike fish in Gorontalo waters.…”
Section: Discussionmentioning
confidence: 89%
“…Sicyopterus longifilis and B. belobranchus have been identified as the two species constituting Nike fish according to Sahami et al (2019). While A. grammepomus has not been previously reported as part of Nike fish, the assumption is made in this research based on the indication in Ali et al (2015) that A. grammepomus is an amphidromous species. Thus, it is considered that these three species collectively make up Nike fish in Gorontalo waters.…”
Section: Discussionmentioning
confidence: 89%
“…During the study, fecundity was found to be low with a mean of 3962 ± 279 eggs per fish. Narejo et al (2002), Rahman et al (2006), Serajuddin and Pathak (2012), and Ali et al (2013) too reported low absolute fecundity. Rahman et al (2012) suggested that low reproductive potential in terms of fecundity was due to the larger size of the ova in Mastacembelus armatus armatus.…”
Section: Discussionmentioning
confidence: 96%
“…Though Mastacembelus armatus is an important species found in the river Ganga, there is a lack of literature on the reproductive biology of this species from this river. A few studies on different vistas of the reproductive biology of M. armatus have been reported from different parts of the world (Gupta 1974, Narejo et al 2002, Rahman et al 2012, Serajuddin and Pathak 2012, Ali et al 2013. The presently reported investigation aimed to report different aspects of reproductive biology, including weight-length relation, sex ratio, hepatosomatic index, relative condition factor, gonadosomatic index, spawning season, L 50 , and fecundity of M. armatus inhabiting the river Ganga.…”
Section: Introductionmentioning
confidence: 99%
“…M. armatus is one of the most popular table fishes with delicious flesh quality having a special flavor, characteristic texture and high protein, oil and vitamin C content. Its market value is double than that of carp species in Bangladesh (Rahman et al, 2006;Ali et al, 2013). Although the estimated area of occupancy and extent of occurrence of M. armatus indicate its wide distribution throughout its range, the reduction of its population was easily speculated based on local accounts collected through field visits and personal communication with local people.…”
Section: Introductionmentioning
confidence: 99%